Stakeholders' Perspectives of Healthcare Commodities Supply Chain Management Practices, Processes, and Challenges: Implications for Achieving Universal Health Coverage in Southeast Nigeria. - Adaora, Uzochukwu Chinelo; Emmanuel, Agbaeze N.; Chudi, Uzochukwu Benjamin (British Journal of Healthcare and Medical Research, 2023)
Healthcare commodities supply chain management is critical for achieving universal health coverage (UHC). In Southeast Nigeria, healthcare commodities supply chain management faces several challenges, including inadequate infrastructure, poor logistics systems, and inadequate human resources. Understanding stakeholders' perspectives of healthcare commodities supply chain management practices, processes, and challenges is essential for improving supply chain performance and achieving UHC. The objectives are to: explore stakeholders' perspectives of healthcare commodities supply chain management practices, processes, and challenges in Southeast Nigeria, identify gaps and challenges in healthcare commodities supply chain management and provide recommendations for improving healthcare commodities supply chain management practices and processes to achieve UHC in Southeast Nigeria. This study used a qualitative approach. We conducted in-depth interviews among 30 key stakeholders involved in healthcare commodities supply chain management in Southeast Nigeria. Stakeholders included healthcare supply chain managers and programme officers. We used a purposive sampling technique to select participants based on their involvement in healthcare commodities supply chain management. Data were analyzed using a thematic analysis approach. The supply chain management practices within the States is the pull system and the processes which include, selection, quantification, procurement, storage, inventory management, distribution, and logistics management information systems are done differently in the States. Several factors affect supply chain management in southeast Nigeria, and these include material, human and financial resources as well as policy issues. The study's findings will be relevant to policymakers, healthcare providers, and supply chain managers in Nigeria and other low- and middle-income countries facing similar challenges.